A Performer-Controlled Live Sound-Processing System: New Developments and Implementations of the Expanded Instrument System. - Gamper, David; Oliveros, Pauline (Leonardo Music Journal, 1998)
Deals with the development and implementation of the Expanded Instrument System (EIS) in December 1998. Ways in which the configuration of the EIS has been used in music compositions; Reasons for the retention of outdate analog technologies in the EIS to after adaptation; Roots of technical developments in EIS.